2022
DOI: 10.1049/cmu2.12562
|View full text |Cite
|
Sign up to set email alerts
|

Deep reinforcement learning‐based joint optimization of computation offloading and resource allocation in F‐RAN

Abstract: The fog radio access network (F-RAN) has been regarded as a promising wireless access network architecture in the fifth generation (5G) and beyond systems to satisfy the increasing requirements for low-latency and high-throughput services by providing fog computing. However, because the cloud computing centre and fog computing-enabled access points (F-APs) in the F-RAN have different computation and communication capabilities, it is crucial to make an efficient computation offloading and resource allocation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Techniques like Target Networks and gradient clipping enhance stability and speed. After 2000 episodes, this approach outperforms traditional Q-learning by over 15%, demonstrating significant improvements in resource allocation efficiency [7].As shown in Figure 2.…”
Section: Training Algorithmmentioning
confidence: 85%
“…Techniques like Target Networks and gradient clipping enhance stability and speed. After 2000 episodes, this approach outperforms traditional Q-learning by over 15%, demonstrating significant improvements in resource allocation efficiency [7].As shown in Figure 2.…”
Section: Training Algorithmmentioning
confidence: 85%
“…In order to optimize the energy utilization efficiency of electric buses and extend the power system life, Huang et al proposed to construct an energy management model, validated the effectiveness of the model, and found that the model effectively extended the life of the battery and improved the efficiency of energy utilization, which, in turn, reduced the total operating cost, and the model made a contribution and had practical application value [ 11 , 12 , 13 ]. To optimize the computational performance and resource allocation capacity of a fog computing wireless access network, Jo et al proposed to construct a computational task offloading and resource allocation strategy, validated the effectiveness of the proposed optimization strategy, and found that this strategy significantly improved the system processing efficiency and resource allocation compared with the traditional processing methods [ 14 ]. In the transportation system, the logistics path-planning performance is insufficient and there is the problem of long computation times, so Yu et al proposed the deep reinforcement learning mechanism to optimize the logistics path-planning model to verify the model’s effectiveness, and found that the computation time of the model compared with the traditional model was significantly shortened, and the phase of the computation time in the path planning was better [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Herein, because discrete and continuous variables are intermingled and continuous variables have infinite values, the DQN scheme cannot be utilized directly. The size of the action space increases exponentially as the discrete level expands, leading to a reduction in performance since discretizing a continuous variable into a finite level will result in quantization error [48]. To address the problem of continuous variables, we developed the DDPG-based algorithm.…”
Section: Algorithm Description and Complexity Analysismentioning
confidence: 99%